Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar di BEI Tahun 2024) - Riseyna Amanda Ajietya; Heri Susanto; Mulyana Gustira Putra (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the effect of Company Size, Leverage, and Profitability on Company Value in banking companies listed on the Indonesia Stock Exchange (IDX) in 2024. The sample in this study consists of 16 banking companies selected based on certain criteria through the purposive sampling method, which is included in the non-probability sampling category. Hypothesis testing was carried out using multiple linear regression. The results of the study show that company size has a positive but insignificant effect on company value, leverage has a negative and significant effect on company value, while profitability has a positive and significant effect on company value. The F test shows that Company Size, Leverage, and Profitability simultaneously have a significant effect on Company Value.